Discovery of novel pyrazolopyrimidine derivatives as potent mTOR/HDAC bi-functional inhibitors via pharmacophore-merging strategy - Zhang, Mingming; Wei, Wei; Peng, Chengjun; Ma, Xiaodong; He, Xiao; Zhang, Heng; Zhou, Mingkang (Bioorganic & medicinal chemistry letters, 2021)
[Display omitted] •Structurally novel mTOR/HDAC bi-functional inhibitors featuring pyrazolopyrimidine core were discovered.•Compound 50 exhibited remarkably potent inhibitory activity against mTOR and HDAC1.•Compound 50 exerted dramatically enhanced anti-proliferative activity against MV4-11 cell line than MLN-0128 and SAHA.•Compound 50 concurrently modulated mTOR signaling and HDAC at cellular level.•Compound 50 displayed selectivity for some specific HDAC subtypes. The mTOR and HDAC dual suppression is meaningful for counteracting drug resistance resulted from kinase mutation and bypass mechanisms. Herein, we communicate our recent discovery of a novel structural series of mTOR/HDAC bi-functional inhibitors featuring the pyrazolopyrimidine core via pharmacophore-merging strategy. More than half of them exerted potent dual-target inhibitory activities. In particular, compound 50 exhibited IC50 values of 0.49 and 0.91 nM against mTOR and HDAC1, respectively, along with remarkably enhanced anti-proliferative activity (IC50 = 1.74 μM) against MV4-11 cell line than mTOR inhibitor MLN-0128 (IC50 = 5.84 μM) and HDAC inhibitor SAHA (IC50 = 8.44 μM). Its intracellular intervention of both mTOR signaling and HDAC was validated by the Western blot analysis. Moreover, as the first disclosed mTOR/HDAC dual inhibitor with selectivity for some specific HDAC subtypes, it has the potential to alleviate the adverse effects resulted from pan-HDAC inhibition. Attributed to its favorable in vitro performance, compound 50 is valuable for further functional investigation as a polypharmacological anti-cancer agent.